Synthesis and Magnetic Properties of Two‐Step‐Coordination Schiff Base Clusters. Issue 26 (26th June 2021) - Peters, Laurens C. J. M.; Engelkamp, Hans; Zeitler, Uli; Christianen, Peter C. M.; Tinnemans, Paul; Maan, Jan‐Kees; Rowan, Alan E.
Abstract: A new family of paramagnetic coordination compounds based on a diimine‐pyridine pincer ligand has been prepared, using a two‐step synthetic approach. The sequential introduction of identical or different transition metals (Co, Mn, Ni, Zn) afforded mono‐, di‐, tri‐ and tetranuclear clusters, whose crystal structure has been determined. Magnetic studies reveal that the metals within the trinuclear manganese cluster engage in a small ferromagnetic exchange interaction ( J =0.15 K). These studies enable the design of new clusters with specific magnetic properties. Abstract : In the quest for single molecule magnets (SMMs), several new homo‐ and heterometallic (Co, Mn, Ni, Zn) paramagnetic coordination compounds have been synthesized, based on a rigid diimine‐pyridine pincer ligand. X‐ray crystallography reveals their structure, while magnetic studies reveal ferromagnetic exchange interactions in some of them.